5-fluorocytosine susceptibility of pathogenic fungi in the presence of allopurinol: potential for improving the therapeutic index of 5-fluorocytosine. - Kerkering, T M (1983)
The minimal inhibitory concentration of 5-fluorocytosine in 18 pathogenic fungal isolates was not altered by either allopurinol (100 microM) or oxypurinol (100 microM). Since allopurinol at this level clinically has been demonstrated to interfere with 5-fluorouracil anabolism, thereby reducing toxicity owing to 5-fluorouracil, allopurinol may be useful in counteracting the 5-fluorouracil-induced myelotoxicity observed in patients being treated with 5-fluorocytosine without interfering with the antifungal activity of 5-fluorocytosine.